Masking and Unmasking the Subject(s): Julián Ríos’s "Puente de Alma" - Durham, Carolyn A. (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Given the intricacy and critical inexhaustibility of Puente de Alma, this essay, despite the promise of its title, can necessarily explore only a limited number of the subjects and textual strategies at play in the text. Moreover, as we will see, the paths one chooses to follow into and through Ríos’s dense, labyrinthine, multilayered “tower of Babel” have as much, if not more, to do with the activity of the reader than with that of the writer.